Inflammation and Aortic Pulse Wave Velocity: A Multicenter Longitudinal Study in Patients With Inflammatory Bowel Disease. Issue 3 (5th February 2019) - Zanoli, Luca; Ozturk, Kadir; Cappello, Maria; Inserra, Gaetano; Geraci, Giulio; Tuttolomondo, Antonio; Torres, Daniele; Pinto, Antonio; Duminuco, Andrea; Riguccio, Gaia; Aykan, Musa B.; Mulé, Giuseppe; et al.
Abstract : Background: Inflammatory bowel disease (IBD) is characterized by a low prevalence of traditional risk factors, an increased aortic pulse‐wave velocity (aPWV), and an excess of cardiovascular events. We have previously hypothesized that the cardiovascular risk excess reported in these patients could be explained by chronic inflammation. Here, we tested the hypothesis that chronic inflammation is responsible for the increased aPWV previously reported in IBD patients and that anti‐TNFa (anti‐tumor necrosis factor‐alpha) therapy reduce aPWV in these patients. Methods and Results: This was a multicenter longitudinal study. We enrolled 334 patients: 82 patients with ulcerative colitis, 85 patients with Crohn disease, and 167 healthy control subjects matched for age, sex, and mean blood pressure, from 3 centers in Europe, and followed them for 4 years (range, 2.5–5.7 years). At baseline, IBD patients had higher aPWV than controls. IBD patients in remission and those treated with anti–TNFa during follow‐up experienced an aortic destiffening, whereas aPWV increased in those with active disease and those treated with salicylates ( P =0.01). Disease duration ( P =0.02) was associated with aortic stiffening as was, in patients with ulcerative colitis, high‐sensitivity C‐reactive protein during follow‐up ( P =0.02). All these results were confirmed after adjustment for major confounders. Finally, the duration of anti–TNFa therapy was not associated with the magnitude of the reduction in aPWV at the end of follow‐up ( P =0.85). Conclusions: Long‐term anti–TNFa therapy reduces aPWV, an established surrogate measure of cardiovascular risk, in patients with IBD. This suggests that effective control of inflammation may reduce cardiovascular risk in these patients.